Peran Edukasi dalam Pencegahan Penyebaran Tuberkulosis di Sekolah - Sabneno, Ade Shianti; Pay, Herlin Priscila; Faot, Maria Irena; Arkian, Teobaldus Andrianus; Mokola, Reashly; Weraman, Pius (Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. This disease is one of the main causes of global morbidity and mortality, with Indonesia being the country with the second highest TB burden in the world. This study aims to evaluate the role of health education in increasing school students' knowledge about TB prevention. The research method used a cross-sectional design with data collection by accidental sampling on 52 high school students who participated in UKS and UKGS activities at the UPT Puskesmas Noebana, November 2024. Knowledge level data was collected through questionnaires before and after the education session. The research results showed a significant increase in students' knowledge, where the